Through the frozen mountains : the 45th Infantry Division in the Vosges Campaign, 20 September 1944- 23 January 1945. - Bishop, Darrell C. (My University, 2015)
The purpose of this study is to examine the Vosges Mountain Campaign of World War II to better the fighting in southern France between the Wehrmacht and the Allies in particular the 45th Infantry Division. Keith Bonn, in When the Odds were Even, was the only historian to write an in-depth review of the campaign. He concluded that the Germans were fighting to hold the mountains and that the American push through the Vosges proved the superiority of the American army. He overlooked that the Germans were fighting a delaying defense and that the odds were far from even. The study draws upon military documents from the 45th Infantry Division, units linked to the Division and documents from Army Group G. It also uses the TruppenfuÌˆhrung (German Army Manuel) for information on the German delaying defense of World War II. It also draws upon various secondary sources for the historiography and background for the study. Chapter one covers the historiography of the debate over the Broad Front versus the Narrow Front along with the historiography of the southern prong of the Broad Front. Chapter two introduces the two sides fighting in the Vosges, the tactic of a delaying defense and the history of the mountains. Chapter three covers the German delaying defense from the Moselle River to the foothills of the Low Vosges. Chapter four covers Operation Nordwind, the German counterattack of January 1945, designed to push the Allies back into the mountains. The thesis promotes an understanding that Army Group G fought a delaying defense in the Vosges Mountains. It had four lines of resistance in the area, first at the Moselle River, then the high Vosges foothills, inside the mountains and then in the foothills of the low Vosges. In the TruppenfuÌˆhrung, the Germans outlined the tactics for a delaying defense. They used pillboxes, dugouts, dummy fortifications, barbed wire, roadblocks, mines, and booby-traps. They refused to maintain contact with the Americans unless in a fortified town. They continued to fall back to new defensive lines. When the Allies threatened to cross the Rhine River, the Germans counterattacked in Operation Nordwind. Army Group G received terrible reinforcements from all over Nazi occupied territory. Army Group G lacked the necessary supplies to fight the campaign and it suffered from poor communication between the units. The 45th Infantry Division had a far better logistical situation than the Germans had in the battle for the Vosges. The odds in the Vosges were against the Wehrmacht and their only hope was to fight a delaying defense in order to slow the Allied advance to the Rhine River.
Keywords: Vosges, Battle of the, France, 1945; Operation Nordwind, 1944-1945; Colmar, Battle of, France, 1945; Military history; World history; American history; 45th Infantry Divison; Army Group G; Seventh Army; Southern France; VI Corps; Vosges Mountains